Odpowiedzi

2010-02-01T17:23:55+01:00
( x - y = 3
( x - 2y = 1 /*(-1)


( x-y=3
( -x+2y=-1
----------------------------
y=2
x-2=3
x=3+2


( x=5
( y=2

Mam nadzieję, że to Ci pomoże;)
2010-02-01T17:24:19+01:00
X-y=3 / +y
x-2y=1

x=3+y
3 + y - 2y = 1

x=3+y
3 - y = 1 / -3

x = 3 + y
y = 2

x = 5
y = 2
  • qb4
  • Początkujący
2010-02-01T17:26:04+01:00
X-y=3
x-2y=1

x=3+y
x-2y=1

x=3+y
3+y-2y=1

x=3+y
y=1-3

x=3+y
y=-2

x=3+(-2)
y=-2

x=1
y=-2

Jak chcesz to sprawdzenie:
x-y=3

1-(-2)=3
1+2=3
3=3
L=P
Chyba dobrze :P